PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN TARIF PAJAK TERHADAP KEPATUHAN WPOP DENGAN RELIGIUSITAS SEBAGAI PEMODERASI - Yasmina Hana Khayla, (2023)
This study aims to determine whether there is an influence of tax knowledge, taxpayer awareness and tax rates on individual taxpayer compliance and moderated by tax socialization. This study used quantitative methods with a sample of individual taxpayers at KPP Pratama Kebayoran Lama Jakarta. The sampling technique uses purposive sampling with a sample of 154 respondents. Data is processed and tested using the SEM-PLS method with the SmartPLS 3.0 application. The test results show that taxation knowledge and taxpayer awareness have a significant effect on taxpayer compliance, while tax rates have no effect on taxpayer compliance. Then religiosity can not strengthen the influence of tax knowledge, taxpayer awareness and tax rates on taxpayer compliance.